Effect of nanoporous thin silica films on interface microstructure and bond strength of cementitious grouts. (24th May 2021) - Muñoz, Jose F.; De la Varga, Igor; Spragg, Robert P.; Graybeal, Benjamin A.; Arnold, Terence S.
Highlights: QIA showed how NPTF modify the microstructure of the grout-concrete interface. NPTF promoted the growth of C-S-H at the grout-concrete interface. The tensile bond strength of the grout-concrete interface improved with NPTF. NPTF are a cost-effective solution to improve bond strength of these interfaces. Abstract: As in many interfaces found within cement-based materials and structural systems, the interface between field-cast grout connections and prefabricated bridge elements (PBE) is a region susceptible to accelerated deterioration. Ensuring a good quality grout-concrete interface is crucial in reducing maintenance costs of the PBE connections and enhancing the service life of the overall structural system. This study continued previous work on the effect of nanoporous thin films (NPTF) of colloidal silica as surface preparation technique to increase the bond strength between the precast components and the field-cast grout. The new work focuses on the influence of the NPTF on the microstructure of the interface between a cementitious grout and a conventional concrete. Important variables of the NPTF, such as application rate and dosage, were evaluated. Changes in the interface microstructure induced by the presence of NPTF were studied through a quantitative image analysis (QIA) and correlated with improvements in the bond strength measured using "pull-off" bond tests. The formation of calcium silicate hydrate (C-S-H) triggered by the reaction of the NPTF with portlandite at the interface was identified as the main contributor to the increase in bond strength. The benefits in the bond strength of the interface rendered by the presence of NPTF were compared against other common surface preparation techniques, such as sandblasting or exposed aggregates via in-form retarders. The results showed that it might be possible to reduce the need for these costly and cumbersome surface preparation techniques.